2017
DOI: 10.1590/0100-29452017746
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mangabeira Trees and Fruits in the Savannah-Restinga Transition Zone

Abstract: ABSTRACT-Brazil is the third largest fruit producer in the world, but many native fruits remain underexploited, as is the case for mangabeira (Hancornia speciosa Gomes). Little is known about general aspects of this species in its naturally occurring environment. Thus, this study aimed to characterize plant and fruit morphologies from native mangabeira selections in the Savannah-Restinga vegetation transition zone. The experiment was carried out in Patizal, Recanto and Recurso villages located in the Morros mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Among the physical analyses, there was a positive correlation between fresh mass and transverse diameter (r ¼ 0.85). This result corroborates Silva et al (2017), who found a positive relation for this variable working with mangaba tree in the Cerrado of Maranhão.…”
Section: Research Resultssupporting
confidence: 91%
“…Among the physical analyses, there was a positive correlation between fresh mass and transverse diameter (r ¼ 0.85). This result corroborates Silva et al (2017), who found a positive relation for this variable working with mangaba tree in the Cerrado of Maranhão.…”
Section: Research Resultssupporting
confidence: 91%
“…speciosa predominantly inhabits the northeastern region of the Cerrado, typically in sandy soils and under low rainfall (Chaves et al 2020). Silva et al (2017) evaluated four populations of this variety in a Cerrado-Restinga ecotonal zone with low fertility soil in the state of Maranhão, Brazil, and obtained mean values of 338, 330, 280, and 172 fruits per plant. Thus, the relative inferiority of H. speciosa var.…”
Section: Discussionmentioning
confidence: 99%